Answer:
[tex]y = \frac{1}{2}x^{2} - 3x + 11.5[/tex]
Step-by-step explanation:
Vertex Form of a quadratic equation;
[tex]y = a( x - h )^{2} + k[/tex]
Vertex of the parabolas (h, k)
The vertex of the parabola is either the minimum or maximum of the parabola. The axis of symmetry goes through the x-coordinate of the vertex, hence h = -3. The minimum of the parabola is the y-coordinate of the vertex, so k= 7. Now substitute it into the formula;
[tex]y = a ( x + 3 ) ^{2} + 7[/tex]
Now substitute in the given point; ( -1, 9) and solve for a;
[tex]9 = a( (-1 ) + 3)^2 + 7\\9 = a (2)^{2} + 7\\9 = 4a + 7\\-7 -7\\2 = 4a\\\frac{1}{2} = a\\[/tex]
Hence the equation in vertex form is;
[tex]y = \frac{1}{2}(x - 3)^{2} + 7[/tex]
In standard form it is;
[tex]y = \frac{1}{2}x^{2} - 3x + 11.5[/tex]